Results of a Qualitative Study of Elementary School Teachers' and Parents' Perceptions of Preventing and Overcoming Students' School Failure - E.V. Ovakimyan; R.M. Bayramyan; O.M. Isaeva; O.S. Osipova (Moscow State University of Psychology and Education, 2023)
We present the results of a qualitative research of the perceptions, attitudes, experiences of teachers and parents of elementary school students on the practices used to overcome school failure. We comapred these practices with the recommended methods that have been shown to be effective in various studies. The sample consisted of 35 female informants living in big cities, regional centers, districts, and rural areas, with different levels of education: 20 teachers (M=38) and 15 parents (M=29) of primary school-aged children were recruited for this study. We gathered information by in-depth interview method, teachers and parents shared their views on the methods which help to overcome and prevent school failure in the context of elementary school. Collected interviews were studied using the method of content analysis and comparison of the obtained data by using the coding technique (A. Strauss and J. Corbin). The date revealed the attitudes of teachers and parents about the concept of school failure, reasons for its occurrence and ways to overcome it, we compared the results with the results of national and international researches on this topic. Summarizing the results of the study, we can conclude that, in general, teachers and parents use school failure overcoming strategies according to their own experience, intuition and sometimes use tools and approaches described in scientific studies. The results of this study can be used for building strategies of interaction between schools and families and for planning professional development of teachers.